2003
DOI: 10.1021/ja029537y
|View full text |Cite
|
Sign up to set email alerts
|

Enantiocontrolled Synthesis of 2,6-Disubstituted Piperidines by Desymmetrization of meso-η-(3,4,5)-Dihydropyridinylmolybdenum Complexes. Application to the Total Synthesis of (−)-Dihydropinidine and (−)-Andrachcinidine

Abstract: A conceptually new approach to the enantiocontrolled synthesis of 2,6-disubstituted piperidines was achieved by desymmetrization of meso-2,6-dimethoxy-eta-(3,4,5)-dihydropyridinylmolybdenum complexes. After protection of the piperidine nitrogen as a urethane derived from (+)- or (-)-trans-2-(alpha-cumyl)cyclohexyl (TCC), a sequential, one-pot methoxide abstraction/nucleophilic addition/methoxide abstraction/nucleophilic addition generated good yields of 2,6-disubstituted-eta-(3,4,5)-dihydropyridinylmolybdenum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The Zstereochemistry depicted for 19b and 19d was confirmed by an X-ray diffraction study on compound 19d (see the Supporting Information for details). In comparison to the electron-rich and reactive alkylidene complexes generated from lactonylmolybdenum scaffold 3, the addition of sp 3 Grignard reagents to the lactamyl scaffold 4 led to stable 2-alkylidene-η-3,4,5-pyridinylmolybdenum complexes 20a,b (Table 1, entries 12,13) in excellent yields. No trace of a Friedel-Crafts-like side-reaction with TFAA was observed.…”
Section: Both (±)-3 and (±)-4 And Their High Enantiopurity Versions (mentioning
confidence: 99%
See 2 more Smart Citations
“…The Zstereochemistry depicted for 19b and 19d was confirmed by an X-ray diffraction study on compound 19d (see the Supporting Information for details). In comparison to the electron-rich and reactive alkylidene complexes generated from lactonylmolybdenum scaffold 3, the addition of sp 3 Grignard reagents to the lactamyl scaffold 4 led to stable 2-alkylidene-η-3,4,5-pyridinylmolybdenum complexes 20a,b (Table 1, entries 12,13) in excellent yields. No trace of a Friedel-Crafts-like side-reaction with TFAA was observed.…”
Section: Both (±)-3 and (±)-4 And Their High Enantiopurity Versions (mentioning
confidence: 99%
“…An exploration of the reactivity of 6-phenyl-η-2,3,4-pyranylmolybdenum complex 7a with the electron-deficient alkenes methyl vinyl ketone (MVK) and ethyl vinyl ketone (EVK) revealed unanticipated subtleties of the reaction system. Of the various Lewis acids initially studied (EtAlCl 2 , Et 2 AlCl, Sc(OTf) 3 , TiCl 4 , BF 3 •Et 2 O), EtAlCl 2 was able to initiate a rapid and highly efficient [5+2] cycloaddition between 7a and MVK giving the expected cycloadduct 21a in 91% yield within 30 min. Only the exo isomer of compound 21a was formed (Scheme 7).…”
Section: Brønsted Acid-promoted [5+2] Cycloaddition Reactions With Comentioning
confidence: 99%
See 1 more Smart Citation
“…Liebeskind group developed a highly diastereoselective methoxide abstraction method which relies on the 'desymmetrization' imparted by the chiral N-protecting group (ÀCO 2 R* in 96. 51 As shown in Scheme 27, the 2,6-disubstituted dihydropyridinylmolybdenum complex (À)-97a was provided by methoxide abstraction of (À)-96 with Ph 3 CPF 6 , subsequent addition of MeMgBr, then ionization of the other methoxide with HBF 4 , and addition of PhMgBr. When reversing the order of nucleophiles added (PhMgBr then MeMgBr), they can obtain the other diastereomeric (+)-97b.…”
Section: Ethermentioning
confidence: 99%
“…In this study, chiral non-racemic stoichiometric molybdenum π-complexes function as enantiomeric scaffolds or organometallic chirons for the rapid enantioselective synthesis of highly functionalized molecules of certain structural complexity. It was demonstrated that pyranyl-and pyridinylmolybdenum scaffolds (1 and 2 , Figure 3), both enantiomeric antipodes of which are readily available, participate in Mo-mediated, regiocontrolled, sequential functionalization at C-2 and C-6 to afford 2,3,6-trisubstituted pyran 31 and piperidine 25,28,32 derivatives. Moreover, they can lead to the rapid assembly of heteroatom-bridged bicyclic ring systems through either [5+2] 23,[33][34][35] or [5+3] 26 cycloaddition processes, or via sequential MukaiyamaMichael and subsequent 1,5-Michael-type reaction.…”
Section: Introductionmentioning
confidence: 99%